Carlos Germán Belli: a mute fetus inhabiting a hole in the periphery - Castillo Cruz, Sandro Jaime (2022)
Considered the most important living poet of Peruvian poetry, Carlos Germán Belli's poetics is characterized by its classical reminiscences and contemporary allusions, which make it an always disconcerting encounter. This occurs, for example, with the figure of his speaker. In this line, this article aims to identify the characteristics of the representation of the speaker in four Bellian poems: «Segregation No. 1», «The valley of feces», «Sextina primera» and «I despite the passing of the years». We argue that the intention of the lyrical subject of these poems is to account for his tragic uniqueness in modern capitalist society, which has deprived him of a poetic, political voice and banished him to inhabit the limits of the human condition.